The development of an instrument to determine the perceptions of Gauteng small business operators of their support systems - Netswera, Fulufhelo Godfrey (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Phil.) -- University of Stellenbosch, 1999.